"Governments, Globalization, and International Business" - Dunning, John H. (Oxford, 2012)
It is a cliche to say that we live in a globalized world in which investment flows, communications, and the operations of multinationals from all parts of the world have changed the character of the international business environment. But the easy concept of globalization poses as many questions as it answers. In this book, a prestigious group of international scholars explores in detail the consequences of globalization--defined as "the deepening structural interdependence of the world economy."